Características epidemiológicos da morbimortalidade por violência em homossexuais na cidade de João Pessoa - PB - Oliveira, Thaisy Sarmento Batista de (2014)
Objective: To identify the epidemiological characteristics of violence against gay, in the João Pessoa (PB) city. Material and methods: Study of documentary and retrospective, with descriptive and inductive approach procedure through indirect observation, conducted from May 2009 to July 2013 in Precinct Specializing in Homophobic Crimes - DECCH and the Institute of Forensic both located in the city of João Pessoa - PB. All data from 315 police reports of the proposed period and their reports of examinations of corpus delicti were collected. The instrument consisted of a particular form, composed of dichotomous or multiple choice questions. The independent variables were: year, month, date, sex, age and day of the week. The dependent variables of the study were: type of violence, the types of occurrences, site of injury, author of aggression, quantification of lesions, location of the affected body parts, kind of soft tissue injury and death occurred. Data were using SPSS version 18, which are subject to descriptive analysis (absolute and percentage distribution). For the bivariate analyzes, the Chi-square and Fisher exact tests, with a significance level of 5% were employed. Results: Among the patients analyzed, the majority of victims were male (83%), aged between 19 and 38 years and 70.7% were classified as mixed (66.6%), with the second incomplete grade (38, 7%). Regarding sexual orientation, 41.5% identified themselves as gay, lesbian 10.8%, 9.2% and 21.5% transvestites transsexuals. Most crime occurs at night 38.5% and 27.7% at dawn, revealing these shifts as more amenable to such affections. With respect to the place of occurrence, the thoroughfare was the scenario with the highest number of assaults 61.5%. The firearm had a predominance among the means of aggression 41.5%, followed by 33.8% stab and blunt objects 16.9%. Body strength and poisonings had the lowest rates 1.5% and 3.1% respectively. Regarding the regions of the body, the chest proved to be the most affected region in coups 49.2%, followed by the head / face 43.1%, 35.4% abdomen, back 27.7%. Still observe a predominance of multiple lesions in 85.7% aggressions. Conclusions: The deadly violence against homosexuals has proved to be an increasingly prevalent problem reported in the media and television. However, research in this area are few. The present work was therefore help to minimize this gap since the information obtained comes from a specialized organ - Police Homophobic Crimes Specialized in - and thereby minimizes possible biases of information. It is important to specify this is information available, the first station based in homophobic crimes already configured in Brazil, located in the city of João Pessoa / PB, though any generalization from the data presented here must be done with care, since it is known that much of what is experienced by homosexuals as aggression is not even communicated to the closest people, much less instances of public power entrusted to prevent and curb the commission of violent acts.